2015
DOI: 10.1177/1087054715588949
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning, Comorbidities, and Behavioral Profiles of Children With ADHD and Disruptive Mood Dysregulation Disorder

Abstract: Children with DMDD were distinguished from children with ADHD-C by their higher comorbidity rate, more impaired behavioral patterns, and family functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…Interestingly, the percentage of securely attached children and mothers in the clinical sample was, respectively, 51% ( N = 43) and 45% ( N = 38), much lower than in the control sample, with 75% ( N = 48) and 66% ( N = 42) of youths and mothers, respectively, displaying secure attachment. This observation confirms that children with DMDD experience difficulties in constructing and maintaining positive affective relationships with their caregivers, as suggested in other studies (American Psychiatric Association, 2013; Bell, 1979; Cerniglia, Cimino, Tafà, & Marzilli, 2017; Cicchetti, Toth, & Handley, 2015; Fonagy & Target, 2005; Sameroff, 1975; Uran & Family, 2015). The mothers of these children, on the other hand, showed low rates of secure attachment to their own mothers.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the percentage of securely attached children and mothers in the clinical sample was, respectively, 51% ( N = 43) and 45% ( N = 38), much lower than in the control sample, with 75% ( N = 48) and 66% ( N = 42) of youths and mothers, respectively, displaying secure attachment. This observation confirms that children with DMDD experience difficulties in constructing and maintaining positive affective relationships with their caregivers, as suggested in other studies (American Psychiatric Association, 2013; Bell, 1979; Cerniglia, Cimino, Tafà, & Marzilli, 2017; Cicchetti, Toth, & Handley, 2015; Fonagy & Target, 2005; Sameroff, 1975; Uran & Family, 2015). The mothers of these children, on the other hand, showed low rates of secure attachment to their own mothers.…”
Section: Discussionsupporting
confidence: 89%
“…For Bella, however, her prolonged instances of angry and irritable mood in between temper outbursts indicated a diagnosis of DMDD. It is also important to note that early onset of ADHD and co-occurring symptoms of anxiety are also consistent with the diagnosis of DMDD (Dougherty et al, 2014; Mulraney et al, 2015; Uran & Kılıç, 2015). …”
Section: Case Conceptualizationmentioning
confidence: 74%
“…For Bella, however, her prolonged instances of angry and irritable mood in between temper outbursts indicated a diagnosis of DMDD. It is also important to note that early onset of ADHD and co-occurring symptoms of anxiety are also consistent with the diagnosis of DMDD (Dougherty et al, 2014;Mulraney et al, 2015;Uran & Kılıç, 2015). Although Bella demonstrated many strengths, such as athletic ability and sense of humor, many of her social experiences became overshadowed by negative interactions, which were interfering with her enjoyment of home and school life.…”
Section: Case Conceptualizationmentioning
confidence: 76%
“…Finally, in Uran's study [30], it appears that children with DMMD have a higher comorbidity rate than those with ADHD. Results showed that DMDD children's average scores were higher than ADHD children in Conners and in "Communication", "Affective Responsiveness", "Affective Involvement" and "General Functioning" subscales of Family Assessment Device (FAD).…”
Section: Distinctionsmentioning
confidence: 91%